Sosialisasi Dan Pemberian Puding Daun Kelor Di Posyandu Mutuah Miko, Kampung Paya Pelu, Kecamatan Silih Nara, Aceh Tengah - Syahidin, Syahidin; Miko, Helmi Tuah; Imtihan, Imtihan; Miranda, Aldi; Abadi, Ahyar; Yusuf, Muhammad; Wandi, Fitra; Anggraini, Juli; Nirwana, Siti; Saddiah, Khalimatu; Mahara, Tasni; Syabaniah, Rani; Masyani, Masyani; Yuliana, Indah; Saris, Relani Simahbengi; Salinawati, Salinawati; Nauli, Marliana Theresa; Kasih, Riski Sintia (Universitas Gajah Putih, Indonesia, 2023)
The quality of nutrition determines the growth of toddlers. Fulfilling food quality using local food ingredients is an alternative that can be developed to produce more innovative food variations. The KKNT activities carried out in Desa Paya Pelu offered the idea of ​​making Moringa Leaf Pudding because of the nutritional content of Moringa leaves. The idea for making Moringa leaf pudding was obtained from site observations and discussions between students and DPL. After getting the idea, the students held discussions with the Payaya Pelu Village government and Mutuah Miko Posyandu cadres to carry out socialization activities and provide moringa leaf pudding. The service activity schedule was carried out on 10-11 October 2023. The activity began with socialization carried out by students to provide an understanding of the nutritional qualities found in Moringa leaves. The students also provided examples of local food ingredients that could be innovated into foods with economic value and high nutrition. According to parents of toddlers, Moringa leaf pudding is a new reference that increases parents' understanding of culinary innovation. The posyandu cadres appreciated the students' activity ideas because they helped provide new understanding to the wider community and it is hoped that similar activities can be carried out on other occasions.